Psychological profile of ice hockey team coach - An Tzin; Biryukova, G. M. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to outline the key psychological traits of an ice hockey team coach using a variety of methods including Standard Multifactor Personality Test (SMPT) and Response to Moving Object Test (RMOT). Subject to the study were 32 coaches. The study data and analysis made it possible to generate an average personality profile of an ice hockey team coach and find, among other things, the following: the lower is the ritualistic aspect in the coach`s personality the higher is his masculinity; the higher is the probability of addictive behaviour (4th scale of SMPT) the higher is the individual control rate. It was also found that the higher skilled coaches (with high qualifications and titles) tend to be more impulsive being psychologically better balanced for their vocational sport activity at the same time and, as a result, their trainees are generally more successful versus the ones of unqualified coaches having no titles.